BUSINESS PERFORMANCE IMPROVEMENT IN RUBBER-PARTS FACTORY THROUGH A QUALITY MANAGEMENT MODEL (CASE STUDY: PTX) - Agustinus Hariadi DP; Sri Hartono; Muhammad Nashar; Wadudi Wibowo; Ani Mekaniwati (Sosiohumaniora, 2022)
A manufacturing plant operating in Banten producing automotive-rubber parts has been experiencing customer complaints increase in period of 2017-2019. Process management contributing to overall quality performance is examined and improved to reduce the problem. This research proposes a model consisting of Top Management Policy, Vendor Control, Employee Participation, Process Management, Quality Performance, Sales Performance and Intangible Performance is proposed. Top management policy provides direction for the vendor control, employee participation encouragement and process control. These three variables simultaneously increase the product quality in the form of conforming requirements, delivering excellent service and minimizing customer complaints. Subsequently, this quality performance improves sales and intangible performance. Respondents of this study were 100 employees of PT. X. PLS software was used to process the data in order to obtain the direction and magnitude of influence between variables referring to the proposed model. The research shows that top management policy has significant effect to vendor control, participation and process control at values of 0.398, 0.480, and 0.487 subsequently. These three variables increase quality of product and service at values of 0.303, 0.426 and 0.188. The quality performance affects intangible at 0.252 but it does not affect sales.